2001
DOI: 10.1093/jn/131.4.1142
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Growth and Skeletal Changes in Zinc-Deficient Growing Rats Are Due to Impaired Growth Plate Activity and Inanition

Abstract: We investigated the effects of dietary zinc deficiency on skeletal metabolism in an animal model. Thirty 21-d-old male Sprague-Dawley rats were fed for 28 d either a zinc-deficient (ZD) diet (1 mg zinc/kg) or a normal diet ad libitum (AL, 50 mg zinc/kg) or in the same quantity as the ZD (pair-fed, PF). Only in the ZD group were general physical signs of zinc deficiency observed. Compared with the AL and PF rats, ZD rats showed significantly lower mean values in ponderal growth rate, femur weight and length, ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
3
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 22 publications
3
65
3
4
Order By: Relevance
“…Leach and Gross (1983) reported, that eggshells from hens fed Mn deficient diet are thinner and show alterations in eggshell ultra structure in mammillary layer and decreased content of hexozamine and hexuronic acid in the organic matrix. There is a lack of literature data on the effect of dietary Zn and Mn on the bone quality in laying hens, but Zn deficiency negatively affected skeletal metabolism in young chickens (Wang et al, 2002) and growing rats (Ovesen et al, 2001;Rossi et al, 2001). …”
mentioning
confidence: 99%
“…Leach and Gross (1983) reported, that eggshells from hens fed Mn deficient diet are thinner and show alterations in eggshell ultra structure in mammillary layer and decreased content of hexozamine and hexuronic acid in the organic matrix. There is a lack of literature data on the effect of dietary Zn and Mn on the bone quality in laying hens, but Zn deficiency negatively affected skeletal metabolism in young chickens (Wang et al, 2002) and growing rats (Ovesen et al, 2001;Rossi et al, 2001). …”
mentioning
confidence: 99%
“…In fact, studies examining effects of Zn deficiency in animal models have shown that mild to severe Zn deficiency disturbs skeletal growth and maturation (Eberle et al, 1999;Wang et al, 2002). Animals fed on Zn-deficient diets have impairment in growth plate chondrocyte proliferation (Rossi et al, 2001;Wang et al, 2002) and bone mass (Eberle et al, 1999). Bone formation in Zn-deficient animals is also characterized by retarded growth plate activity and is associated with reduced cancellous and trabecular volume (Oner et al, 1984;Rossi et al, 2001).…”
Section: Fig1: Lateral View Of the 20-days-old Fetuses Showing The Crmentioning
confidence: 99%
“…Animals fed on Zn-deficient diets have impairment in growth plate chondrocyte proliferation (Rossi et al, 2001;Wang et al, 2002) and bone mass (Eberle et al, 1999). Bone formation in Zn-deficient animals is also characterized by retarded growth plate activity and is associated with reduced cancellous and trabecular volume (Oner et al, 1984;Rossi et al, 2001). …”
Section: Fig1: Lateral View Of the 20-days-old Fetuses Showing The Crmentioning
confidence: 99%
“…Mice in heat group were housed under control group conditions, but additionally subjected to 40°C and 50 ± 5% RH between 12 and 2 p.m. daily, for eight consecutive days during heat treatment period. The whole body heat temperature of 40°C for 2 h was selected on the basis of previous reports of total recovery after heat treatment and feasible parameters for a chronic heat model in mice (Rossi et al, 2001;Li et al, 2013). Following heat treatment each day, feed weight (as a measure of feed intake) and body weights were of all mice were recorded.…”
Section: Experimental Designmentioning
confidence: 99%
“…Zinc has also been found to be an indispensable element in reproduction and is required for the maintenance of germ cells; progression of spermatogenesis; and, regulation of sperm motility (Zhao et al, 2011). The effects of Zn deficiency are similar in most animal species and include dermatitis, alopecia, ocular lesions, testicular atrophy, growth retardation, and anorexia (Rossi et al, 2001). Zinc deficiency in male reproduction results in gonad dysfunction, decreased testicular weight, and seminiferous tubule shrinkage (Bedwal and Bahuguna, 1994).…”
Section: Introductionmentioning
confidence: 99%